Neutron radiation effect on 2N2222 and NTE 123 NPN silicon bipolar junction transistors - Oo, Myo Min; Alang Md Rashid, Nahrul Khair; Abdul Karim, Julia; Mohmamed Zin, Mohamed Rawi; Hasbullah, Nurul Fadzlin (IOP science, 2013)
This paper examines neutron radiation with PTS (Pneumatic Transfer System) effect on silicon NPN bipolar junction transistors (2N2222 and NTE 123) and analysis of the transistors in terms of electrical characterization such as current gain after neutron radiation. The key parameters are measured with Keithley 4200SCS. Experiment results show that the current gain degradation of the transistors is very sensitive to neutron radiation. The neutron radiation can cause displacement damage in the bulk layer of the transistor structure. The current degradation is believed to be governed by increasing recombination current between the base and emitter depletion region.